A QM/MM study of the nature of the entatic state in plastocyanin - Hurd, Catherine A.; Besley, Nicholas A.; Robinson, David (Wiley, 2016)
Plastocyanin is a copper containing protein that is involved in the electron transfer process in photosynthetic organisms. The active site of plastocyanin is described as an entatic state whereby its structure represents a compromise between the structures favored by the oxidized and reduced forms. In this study the nature of the entatic state is investigated through density functional theory based hybrid quantum mechanics/molecular mechanics (QM/MM) molecular dynamics simulations. The strain energy is computed to be 12.8 kcal/mol and 14.5 kcal/mol for the oxidized and reduced forms of the protein, indicating that the active site has an intermediate structure. It is shown that the energy gap between the oxidized and reduced forms varies significantly with the fluctuations in the structure of the active site at room temperature. An accurate determination of the reorganization energy requires averaging over conformation and a large region of the protein around the active site to be treated at the quantum mechanical level.